ANALISIS WACANA KRITIS DALAM RUBRIK”PANDANGAN KAMI” SURAT KABAR “SUMATERA EKSPRES” EDISI AGUSTUS 2016 - asmah asmah (Universitas PGRI Palembang, 2017)
Abstract: Studies on the critical discourse was mostly done by the researchers, evidenced by the many theses and thesis using discourse analysis as